Research Growth in Sharia Accounting and Finance in Indonesia - Dini Dewindaru; Ratna Kusumadewi; Laili Latifah Puspitasari (AFEBI Islamic Finance and Economic Review, 2022)
This study seeks to describe the development of research in Islamic accounting and finance in Indonesia. The in-depth study aims to understand the research topics of published articles and conference papers published in the period of 1997-2018. The results found in samples are grouped into four major research topics: concept, construction, pre-position, and performance assessment. The findings proved that conceptual topics dominated researches conducted in the period 1997-2013, while performance measurement was the dominant topic of the 2014-2018 study period. Based on these findings, it is concluded that research in the field of Islamic accounting and finance in Indonesia is still in the process of growth and development. In addition, this study also discovered a significant increase in the number of articles in the last two years, which indicates a growing and ascending trend in Islamic accounting and finance studies in Indonesia. The research mapping is expected to provide insights into various research topics that have been written and topics that still open for further research.